2009
DOI: 10.1111/j.1537-2995.2008.02036.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet concentrates for bone graft enhancement in sinus lift procedure

Abstract: Topical use of APCs might be helpful in bone reconstruction. No clinical, radiologic, or histologic osteogenesis inhibition of high PLT concentration was observed. The resulting osteogenesis was adapted to dental implant placements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(107 citation statements)
references
References 19 publications
0
104
0
3
Order By: Relevance
“…Biopsies taken after 6 and 7 months did not show any statistical difference. By contrast, BETTEGA et al 2 , RAGHOEBAR et al 22 and SCHAAF et al 24 did not observe any significant difference between both treatments, at the 3 and 6 months evaluations. A meta-analysis of the four included articles failed to show a significant effect of PRP, as the calculated pooled difference [95% CI] in bone fraction was À0.398 [À0.796 to À0.001]; (P = 0.341).…”
Section: Histomorphometric Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Biopsies taken after 6 and 7 months did not show any statistical difference. By contrast, BETTEGA et al 2 , RAGHOEBAR et al 22 and SCHAAF et al 24 did not observe any significant difference between both treatments, at the 3 and 6 months evaluations. A meta-analysis of the four included articles failed to show a significant effect of PRP, as the calculated pooled difference [95% CI] in bone fraction was À0.398 [À0.796 to À0.001]; (P = 0.341).…”
Section: Histomorphometric Resultsmentioning
confidence: 84%
“…Various authors concluded that no relevant differences in healing of soft tissues and bone existed between sites reconstructed with autogenous bone and autogenous bone mixed with PRP 2,22,24 . Four trials evaluated the possible advantage of using PRP to accelerate bone healing for sinus augmentation 2,5,22,24 . No clinical benefit could be observed in a meta-analysis of these studies when using PRP, in other words there is no scientific support for justifying its use in application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Two-stage lateral sinus lift with autogenous corticocancellous blocks from the iliac crest versus granules of bone with platelet concentrates (APCs) and a biologic glue (Tissucol, Baxter SA, Maurepas, France), left to heal for 6 months in a split-mouth trial (Bettega 2009). Plateletpheresis was made at least 3 days before surgery on a plateletpheresis collection system (Trima Accel, Version 5.1, Gambro BCT, Lakewood, CO), a single-needle continuous-flow separation system.…”
Section: Which Is the Most Effective Sinus Lift Procedure? (Nine Triamentioning
confidence: 99%
“…• Bone gain expressed in mm or percentage: vertical bone gain was measured in mm by direct measurement in three trials (Schaaf 2008;Bettega 2009;Felice 2009b), however for two trials (Schaaf 2008;Bettega 2009) data were presented in a way we could not use.…”
Section: Characteristics Of Outcome Measuresmentioning
confidence: 99%